Enhancing User Satisfaction with Local Government E-Government: The Influence of E-Government Quality (E-GovQual) - Rachman*, Adryan; Alvita, Meilisa; Widjadja, William (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
This research aims to enhance the accountability of user satisfaction measurement in E-Government within local government in Indonesia, with a focus on six knowledge aspects and their impact on E-Government services in West Java. The method employed is descriptive and verificative, utilizing a quantitative approach. The heads of sections in West Java local government organizations served as respondents in the survey. User satisfaction with local government E-Government is positively and significantly influenced by usefulness, dependency, trust, functionality and form of interaction, as well as support. The novelty of this research reveals that usability and trust are key factors in improving government websites. For the future, further exploration and diverse ideas are needed to better understand this topic, and attention should be given to user responses and behaviors when using government websites for further improvement.Keywords: User Satisfaction; Quality of E-Government; Ease of Use; Function of Interaction; Content of Information